Comparison of the effect of training with Balance board and Pilates and combined on the static and dynamic balance of elderly women - Masoumeh Mohammadi Arani; Nader Rahnama (Shahid Beheshti University, 2021)
Purpose: Weakness in balance is one of the risk factors for falling, injuries or even death of elderly. Age increases the number of falls and decreases the quality of life. The main objective of this research was to compare the effects of exercises with Balance board and Pilates on static and dynamic balance of elderly women. Methods: From among elderly women located in Isfahan city, 36 persons (with average age of 71±2.4 years old, height of 1.61±0.56 m, weight  of 60±6.4 kg and body mass index of 24.49 kg/m2) were selected and randomly divided into three groups as follows: Pilates exercises (n=12), balance boards exercises (n=12) and combined exercises (n=12); so they performed Pilates exercise plan,  exercise plan related to the balance and simultaneous Pilates and balance board plan for eight weeks, respectively. Before and after the intervention, static and dynamic balance was measured using the stork static balance and Get up and go Test (TUG) Life. Data were analyzed through ANOVA with repeated measures and at the significance level of 0.05. Results: The experimental groups showed a significant difference before and after the intervention in the fear of static and dynamic balance factors (P < 0.05). The comparison of the data between the three groups regarding the static and dynamic balance showed a significant difference before and after the training period, so that the recovery rate in the experimental group of combined exercises was more than the other two groups. Conclusion: The findings indicated that the exercises were effective in the three experimental groups, but the improvement in the experimental group of combined exercises was more than the other two groups, so this protocol can be used as a complementary rehabilitation method to improve the static and dynamic balance of elderly people (P = 0.011).